2004
DOI: 10.14712/18059694.2018.101
|View full text |Cite
|
Sign up to set email alerts
|

Gains and Losses of HLA Class II (DR) and CD4 in Atypical Hyperplasia, Carcinoma in situ and Infiltrating Ductal Carcinoma of the Breast

Abstract: Aim: Breast cancer is a frequent cause of death among women with gynaecologic malignancies despite the introduction of combination chemotherapy. There is therefore a need for new therapeutic strategies for patients with breast cancer, such as cellular immunotherapy. In this immunohistochemical study we analyzed the epithelial expression of major histocompatibility complex (MHC) class II (HLA-DR) on atypical and malignant primary mammary epithelial cells, as well as the magnitude of the stromal T lymphocytes (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…3E). These findings validate the DSP detection of HLA-DR expression in epithelial tumor ROIs www.nature.com/scientificreports www.nature.com/scientificreports/ and confirm that a subset of patient-derived breast cancer epithelial cells can express MHCII proteins such as HLA-DR, which is consistent with our previous observations 2, 3 , as well as with those of other investigators 4,[17][18][19][20][21] .…”
Section: Resultssupporting
confidence: 91%
“…3E). These findings validate the DSP detection of HLA-DR expression in epithelial tumor ROIs www.nature.com/scientificreports www.nature.com/scientificreports/ and confirm that a subset of patient-derived breast cancer epithelial cells can express MHCII proteins such as HLA-DR, which is consistent with our previous observations 2, 3 , as well as with those of other investigators 4,[17][18][19][20][21] .…”
Section: Resultssupporting
confidence: 91%
“…In 4w-11 tumors, CEBPA, which is associated with breast cancer progression [27] was down-regulated and CEBPB, a gene found to be up-regulated in breast cancer as well as mouse mammary tumors [28], is up-regulated. Moreover, the 4w-11 tumors exhibited down-regulation of actin, myosin, Ig, and MHC class 2 transcripts, which have been shown to be decreased in highly metastatic breast cancer cell lines [29], as well as decreased during progression to tumor [30]. 8w-B tumors had up-regulation of PLK [31] and 8w-D tumors had up-regulation of Epha2 [32].…”
Section: Resultsmentioning
confidence: 99%
“…It is not yet known when these antigens appear in the adrenal cortex, but they are probably involved in cellular differentiation. Loss of expression of HLA class antigens or deregulation has been reported in a great variety of tumors, including breast, cervix, larynx, colon, and pancreas cancers [26][27][28][29][30][31][32]. In a study of gene expression by microarray analysis, carried out on 24 pediatric ACTs (5 adenomas, 18 carcinomas, 1 tumor classified as indeterminate for malignancy), West et al [12] identified 52 probe sets for which significant differences were found when comparing adrenocortical adenomas versus carcinomas.…”
Section: Discussionmentioning
confidence: 99%